Pemberdayaan Kaum Awam dalam Pengembangan Pelayanan Gereja untuk Mewartakan Kabar Keselamatan - Rusmanto, Ayub; Dewandaru, Bambang (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2022)
This article presents facts about the dichotomy of ecclesiastical ministry perspective between the ordained (Pastors, Bible teachers and those with theological education background) and the laity (ordinary church members). The church is present in the midst of the world as an announcer of salvation and must convey references and attributes in its mission so that it can organize and help humans to experience the existence and existence of God in an ever-changing world. The church must be responsive and capable of responding to the challenges that become obstacles in carrying out missions in this world. In significance, the dichotomy between the ordained and the laity (ordinary church members) continues to be pursued and fought for in the ministry of the church to proclaim salvation. The method used in this paper is a qualitative descriptive analysis method with a library approach, related literature, journals as the basis for a descriptive discussion to examine the empowerment of the laity in the development of church services to proclaim the message of salvation. The results of this paper prove that the involvement of the laity is very effective and relevant in the vocation and struggle of the ministry in proclaiming the message of salvation in the midst of the congregation and in the field of work. Thus, empowering the laity becomes a call and a continuous struggle that continues to process and can be implemented in real life in the midst of the development of ministry in the church and has an impact in the field of work.AbstrakArtikel ini menyajikan fakta dikotomi cara pandang pelayanan gerejawi antara kaum tertahbis (Pendeta, Guru Injil dan mereka yang berlatar belakang pendidikan teologi) dan kaum awam (anggota-anggota gereja biasa). Gereja hadir ditengah-tengah dunia sebagai pewarta keselamatan harus menyampaikan referensi dan atribut di dalam misinya sehingga dapat menyelenggarakan dan menolong manusia untuk mengalami eksistensi dan keberadaan Allah di dunia yang selalu berubah. Gereja harus tanggap dan cakap menjawab tantangan yang menjadi kendala dalam menjalani misi di dunia ini. Dalam signifikansi dikotomi antara kaum tertahbis dan kaum awam (anggota-anggota gereja biasa) terus diupayakan dan diperjuangkan dalam pelayanan gereja untuk mewartakan keselamatan. Metode yang digunakan dalam karya tulis ini adalah metode kualitatif deskriptif analisis dengan pendekatan kepustakaan, literature, jurnal yang berhubungan sebagai landasan pembahasan secara deskriptif menelisik tentang pemberdayaan kaum awam dalam perkembangan pelayanan gereja untuk mewartakan kabar keselamatan. Hasil karya tulis ini membuktikan keterlibatan kaum awam sangat efektif dan relevan dalam panggilan dan perjuangan pelayanan dalam mewartakan kabar keselamatan di tengah-tengah jemaat dan di lapangan pekerjaan. Dengan demikian, pemberdayaan kaum awam menjadi panggilan dan perjuangan yang berkesinambungan terus berproses dan dapat diimplementasikan dalam kehidupan nyata di tengah-tengah perkembangan pelayanan dalam gereja dan berdampak di lapangan pekerjaan.